Two-generational reproductive toxicity assessment of 6:2 chlorinated polyfluorinated ether sulfonate (F-53B, a novel alternative to perfluorooctane sulfonate) in zebrafish. (December 2018) - Shi, Guohui; Guo, Hua; Sheng, Nan; Cui, Qianqian; Pan, Yitao; Wang, Jinxing; Guo, Yong; Dai, Jiayin
Abstract: As an alternative to perfluorooctane sulfonate (PFOS), 6:2 chlorinated polyfluorinated ether sulfonate (commercial name: F-53B) has been used in the Chinese chrome plating industry for over four decades. It has been increasingly detected in environmental matrices in recent years, causing great concern regarding its potential health risks to humans and wildlife. However, its adverse effects on biota remain largely unknown. To explore the chronic toxicity of F-53B on reproduction, a two-generational study was conducted using zebrafish ( Danio rerio ). Adult zebrafish (F0 generation) were chronically exposed to different concentrations of F-53B (0, 5, 50, and 500 μg/L) for 180 d using a flow-through exposure system, with F1 and F2 generations reared without exposure. The reproductive toxicity endpoints were assessed in F0 and F1 adult fish. Results showed that F-53B accumulated in the F0 gonads and transferred to the F1 generation via maternal eggs, and even remained in F1 adult fish and their eggs (F2) after 180 d depuration. In the F0 generation, F-53B exposure significantly inhibited growth and induced reproductive toxicity, including decreased gonadosomatic index and egg production/female, changes in the histological structure of the gonads, and increased serum testosterone levels. In particular, serum estradiol and vitellogenin levels were significantly increased in 5 μg/L F-53B-exposed adult males. The transcriptional levels of several genes along the hypothalamic-pituitary-gonadal axis were altered in F0 generation fish. Testis transcriptome analysis revealed that F-53B exposure disrupted spermatogenesis in F0 male zebrafish. Maternal transfer of F-53B also induced adverse effects on growth and reproduction in the F1 generation. Furthermore, the higher occurrence of malformation and lower survival in F1 and F2 embryos indicated that parental exposure to F-53B could impair the embryonic development of offspring. Taken together, this study demonstrated that F-53B could induce reproductive toxicity in zebrafish similar to that induced by legacy PFOS, and its potential adverse effects on offspring deserve further investigation. Graphical abstract: Image 1 Highlights: Bioconcentration of F-53B was gender-dependent, and transfer from parent to eggs. Similar to PFOS, F-53B exposure inhibited the growth and reproduction of zebrafish. F-53B exposure altered sex hormone level and expression of genes along HPGL axis. Transcriptome analysis showed F-53B exposure disrupted spermatogenesis in male fish. Parental exposure to F-53B could impair embryonic development of offspring. Abstract : Long-term exposure to F-53B for one generation had adverse effects on reproduction in both F0 and F1 adult fish and impaired embryonic development of offspring.